She dances [videorecording (DVD)] - Gomez, Rick; Zahn, Steve, 1968-; Zahn, Steve, 1968-; Zahn, Audrey; Hawke, Ethan, 1970- (Universal, 2026)
On the road to her final dance competition, Claire and her estranged father Jason are given an unexpected opportunity to reconnect. As pressure mounts and Jason is thrust into the colorful and chaotic world of competitive dance, can they shake off old tensions and move forward together?